Is naming brands in English worth doing? Effects of foreignness and country of origin on brand equity - Rafael Barreiros Porto; Talyta da Silva Soyer (BBR: Brazilian Business Review)
The effect of the brand identity strategies, foreignness and country of origin, on brand equity raises questions about the effectiveness of the names given by entrepreneurs to commercial establishments. This study investigates the influence of foreignness and country of origin on consumer-based brand equity. We conduct a 2x2 between-subjects experiment with 280 participants, using brand foreignness and country of origin as manipulated variables and brand equity as the dependent variable. The results show a positive and direct effect of foreignness on brand equity indicators, associated image and willingness to pay a premium price. Country of origin moderated the relationship between foreignness and brand equity, showing that a brand with foreignness increases exclusivity without any identification of the country of origin and that a brand without foreignness increases the same indicator when the country of origin is present. This research may help in building and managing new product, service, and retail brands.